Development of Sports and Health Physical Education Learning E-Module Pencak Silat Material Accompanied by Physical Fitness Exercise Activities for Class VII Students - Robiatun Batubara; Bafirman Bafirman; Asep Sujana Wahyuri; Nurul Ihsan; Abdur Rahim Fadlan (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to determine the development of sports and health physical education learning e-modules for pencak silat material accompanied by physical fitness training activities for seventh grade students. Research is a type of development research (Research & Development). This research was conducted in class VII SMP Pertiwi Siteba, SMP Angkasa Lanud and SMP IT Budi Mulya, Padang City. The instrument in this study is a questionnaire that has been validated by experts. The data analysis technique is a quantitative descriptive analysis technique. The results of the study concluded that the level of product feasibility was 93.05% and large-scale trials obtained data of 86.21% of students strongly agreed to use the resulting e-learning module. It can be concluded that based on the validation tests and trials conducted, the e martial arts learning module for class VII students is